The nation on social networks and on the brazilian politics - Paula, Luciane de [UNESP]; Alves de Oliveira, FAbio Augusto [UNESP] (Federal Univ Ceara, 2020)
This work is theoretical and methodologically based on the bakhtinian studies and proposes to analyze the conception of nation as an ideological sign, either verbal, vocal, visual or syncretic, expressed by multimodal utterances transmitted on social networks (through the use of the national flag or colors, slogans and other forms) and its function on the present brazilian politics (2018-2019). The digital platforms, in contemporary times, have fulfilled, among others, the function of a discursive arena, where the mos diverse value judgments and social voices are confronted. Three posts from Facebook composes the corpus of this article to the reflection that it proposes. Collected on pages with political nature, the posts bring, more explicitly, the social tension about what is Brazil to different persons and groups. Ideological sign is the concept that holds the analysis undertaken. This article discuss the conflict about the notion of Brazil, on the political sphere, as well the forms of resignification of the ideological sign, in the mediatic circulation. To debate about the role of the ideological sign as a language phenomenon is justified, as theoretical as analytical and socially, by the importance of those environments on contemporaneity. The analysis focus on the discursive functioning of spheres that, increasingly, are confused, in official and non-official interaction. The results reveal how much the social networks (here exemplified by the Facebook) are the life of the discursive sign that reflects and refracts the practice as a social act.
Keywords: Bakhtinian studies; ideological sign; Nation